Faktor-Faktor yang Mempengaruhi Penggunaan Electronic Procurement terhadap Kinerja pada Bagian Pengadaan Universitas Brawijaya - Yudharini, Shinta; Saleh, Choirul; Pratiwi, Ratih Nur (Jurnal Ilmiah Administrasi Publik, 2021)
The purpose of this research is to determine the factors that affect the use of Electronic Procurement on the performance of employees of the Public Service Agency (BLU) (Case Study on the Procurement of Goods and Services, Universitas Brawijaya). The method used is a quantitative method, the population opened is 97 people, consisting of 65 users/ user E-Procurement in Brawijaya University environment and 32 people are businessmen who participated in the auction in 2019. Thw data analysis uses quantitative with simple and multiple linear regression test equipment, t test, F test, correlation test and determination. The result of data processing shows that the Expectancy Performance positively affects the interest of E-Procurement, Effort Expectancy has no effect on the interest in E-Procurement use. Social Influence does not affect the interest of E-Procurement. Facilitating Conditions have positive effect on E-Procurement usage behavior, and interest in use has no effect on E-Procurement use behavior.